O możliwości zastosowania teorii prawa Zygmunta Ziembińskiego w rozstrzyganiu problemów bioetycznych - Łukasz Moniuszko (Studia Ecologiae et Bioethicae)
The article looks at attempts to use the legal and moral concepts of Zygmunt Ziembiński in bioethical considerations. Assuming that law is determined by morality, an example of an unborn child is used to examine how these combined factors can be applied in bioethics. According to the author, the most interesting aspects are the proposals formulated by Ziembiński. In his opinion, the liberal theory of Ziembiński’s law, which expands on the views of Maria Ossowska and Czeslaw Znamierowski, deserves special attention. In summing up, the author comes to the conclusion that the concept of Ziembiński’s law can find universal application in bioethics, thanks to its more than subjective practical applicability.